2011
DOI: 10.1093/infdis/jir281
|View full text |Cite
|
Sign up to set email alerts
|

Until Which Age Should Women Be Vaccinated Against HPV Infection? Recommendation Based on Cost-effectiveness Analyses

Abstract: Not only HPV vaccination of girls before sexual debut is a highly effective and cost-effective strategy for prevention of cervical cancer, but also vaccination of women until the age of 25 years is generally cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 34 publications
0
42
0
3
Order By: Relevance
“…In the context of health economic studies, several studies in the Netherlands confirmed that screening of HPV coupled with vaccination was cost-effective, compared with screening only [14][15][16][17]. Also, the influence of catch-up vaccination for older women [18], vaccination of young boys, combination of various screening methods and intervals [19] and reductions in vaccine dosing [20] have been explored.…”
mentioning
confidence: 99%
“…In the context of health economic studies, several studies in the Netherlands confirmed that screening of HPV coupled with vaccination was cost-effective, compared with screening only [14][15][16][17]. Also, the influence of catch-up vaccination for older women [18], vaccination of young boys, combination of various screening methods and intervals [19] and reductions in vaccine dosing [20] have been explored.…”
mentioning
confidence: 99%
“…This is consistent with other reports even though adapted to other country specific settings, that extending HPV vaccination beyond young girls may be effective and cost-effective. In the Netherlands, an evaluation using a Markov model found that HPV vaccination remained generally cost-effective in women up to age 25 years [29], and some countries such as Australia [13] and the US [14] already recommend HPV vaccination up to age 26 years. Adult women remain at risk of HPV infection from new sexual relationships, and the protective effect of HPV vaccination against cancer may be seen more quickly in adult women than after vaccination of adolescent girls [30].…”
Section: Discussionmentioning
confidence: 99%
“…5 A infeção pelo HPV é condição necessária na quase totalidade dos casos de CCU, [5][6][7][8][9][10] existindo mais de 100 genótipos do HPV estudados; 90% dos casos de CCU são provocados pelos genótipos de alto risco (oncogénicos) 16,18,45,31,33,52, 58 e 35. 5,[10][11][12][13][14] A infeção pelos genótipos 16 e 18 está na origem da grande maioria dos casos de CCU Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Ribeiro JP, et al Eficácia das vacinas contra o HPV nas mulheres com mais de 24 anos na prevenção do CCU, Acta Med Port 2016 Jun;29 (6): [401][402][403][404][405][406][407][408] -mais de 70% dos casos, 5,6,10,[14][15][16][17] enquanto aproximadamente 10% são consequência da infeção pelos genótipos 45 e 31, 15 e os restantes são causados por outros genóti-pos oncogénicos. Esta infeção é uma doença sexualmente transmissível, representando uma das mais comuns, 11,12,14 o genótipo 16 é o mais prevalente, 12 apesar de existir variação geográfica na prevalência dos genótipos.…”
Section: Introductionunclassified
“…18,19 A maioria das infeções por HPV é transitória, 6,15 ocorrendo resolução espontânea em 90% dos casos após dois anos, 15 que, no entanto, não confere imunidade contra a infeção pelo vírus. 6,9,12,13,15,16 A eficácia das vacinas contra o HPV nas mulheres até aos 25 anos de idade está bem comprovada, 10,11,16,17,19 porém, a eficácia em idades superiores ainda não está totalmente estabelecida e existem dúvidas quanto à sua utilização.…”
Section: Introductionunclassified
See 1 more Smart Citation